Which equation, when solved, results in a different value of x than the other three?


-7/8x-3/4=20

3/4+7/8x=-20

-7(1/8)x-3/4=20

-7/8(-8/7)x-3/4=20(-8/7)

Respuesta :

Let's solve this:
I'm going to assume that -7/8x and those similar are (-7/8) times x and so on.
from first glance, the fourth equation looks like a failed attempt at a modifier of the first equation.
Start: First equation:
 -(7/8)x - (3/4) = 20
multiply both sides of the equation by -1 to make it the 2nd equation:
(7/8)x + (3/4) = -(20)
 
or to get the third equation from the first, distribute the numerator in -(7/8)x outside the parentheses (remember: top/bottom = top times 1 over bottom) :
- 7(1/8)x - (3/4) - 20
equation 4 is weird (lets try to derive the first one from it):
-(7/8)(-8/7)x - (3/4) = 20(-8/7)
divide to 'get rid' of the (-8/7)
-(7/8)x - (3/4)/(-8/7) = 20
first and third terms are right but the second isn't; therefore, the 4th equation is the different one

Answer:

d

Step-by-step explanation:

trust me